Clinical problems related to human parvovirus B19, including protracted anemia in AIDS and other forms of immunodeficiency - Setúbal, Sérgio; Oliveira, Solange A.; Angelis, Flávia De; Seródio, Ana Cristina; Nascimento, Jussara P. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
The fortuitous discovery of Human Parvovirus B19 in 1974 made possible to establish the etiology of some long known clinical syndromes, now definitely linked to the infection with this virus. After a literature review, these syndromes are described, as well as the events that made possible to link them with parvovirus B19, in the approximate sequence in which these events occurred. Brazilian literature was also reviewed. The text also addresses parvovirus B19 infection in AIDS and other forms of immunodeficiency.